Pengembangan Sistem Informasi Pengelolaan Penjualan Keripik Buah Pada CV KAJEYE FOOD Dengan Metode Peramalan Permintaan Menggunakan Model Waterfall - Arib Rahman Sutrisna; Niken Hendrakusma Wardani; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
CV KAJEYE FOOD is a company that engaged in fruit processing, especially chips and candied fruit that called SoKressh & Kenyil. The recap process of fruit chips sales is still done manually. It takes time and has possibility of human error that caused the error information. The company sometimes experience over-production in the fruit chips production, so it can cause harm to the company. The company needs information system that can manage the sales and can predict the demand of fruit chips in the next period. Development of information systems using waterfall method that starts from requirement analysis, design, implementation and testing. Design and implementation using structural approach (Data Flow Diagram, Entity Relationship Diagram and State Transition Diagram). Implementation of sales management information system is web-based and uses exponential smoothing and moving averages method in forecasting demand. The test results using white-box and black-box method indicate that all function of system run well according to requirement and design. Testing of forecasting method of exponential smoothing and moving averages shows that exponential smoothing method with constant 0.9 is the most accurate forecasting method, with mean absolute deviation of 924.5, mean square error of 876,752.5 and mean absolute percent error of 26.1%.